2012
DOI: 10.1021/jp208852r
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Electron-Transfer Dynamics in Ionic Liquids and Neutral Solvents

Abstract: The effect of ionic liquids on photoinduced electron-transfer reactions in a donor−bridge−acceptor system is examined for two ionic liquid solvents, 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide and tributylmethylammonium bis(trifluoromethylsulfonyl)amide. The results are compared with those for the same system in methanol and acetonitrile solution. Electron-transfer rates were measured using time-resolved fluorescence quenching for the donor− bridge−acceptor system comprising a 1-N,1-N-dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 60 publications
(117 reference statements)
2
60
0
Order By: Relevance
“…11,[33][34][35][36] In several cases, it was found that the reactions in ILs exhibit distributed dynamics and are often solventcontrolled. 11,36 Previously, Lee, et al, compared ET dynamics in ionic liquids and neutral solvents by investigation of a D-B-A complex consisting of DMPD as electron donor connected to the excited-state acceptor coumarin 343 (C343) by a proline bridge. Using time-resolved fluorescence, the excited state dynamics of DMPD-Pro 1 -C343 (P1 ) was studied in the neutral solvents acetonitrile and methanol, and in two ILs based on the bis(trifluoromethylsulfonyl)amide (NTf − 2 ) anion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,[33][34][35][36] In several cases, it was found that the reactions in ILs exhibit distributed dynamics and are often solventcontrolled. 11,36 Previously, Lee, et al, compared ET dynamics in ionic liquids and neutral solvents by investigation of a D-B-A complex consisting of DMPD as electron donor connected to the excited-state acceptor coumarin 343 (C343) by a proline bridge. Using time-resolved fluorescence, the excited state dynamics of DMPD-Pro 1 -C343 (P1 ) was studied in the neutral solvents acetonitrile and methanol, and in two ILs based on the bis(trifluoromethylsulfonyl)amide (NTf − 2 ) anion.…”
Section: Introductionmentioning
confidence: 99%
“…From the 16 starting conformations, 8 distinct conformations corresponding to local energy minima were obtained. The five lowest-energy conformations and energies relative to the lowestenergy conformer are shown in Figure 6.Results and DiscussionLee, et al, characterized the dynamics of electron transfer from DMPD to C343 in a D-B-A system utilizing a single proline bridge (DMPD-Pro-C343, P1 ) 36. In this system, only a single low-energy conformation was obtained using geometry optimization methods…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9−14 Time-resolved fluorescence measurements of rates on picosecond time scales demonstrate significant heterogeneities in rates of intramolecular charge shifts. 15,16 Much of the heterogeneity in IL solvation dynamics arises because the viscosities are typically 1−3 orders of magnitude larger than for typical neutral solvents. 8 Bimolecular electron-transfer rates in ILs are not well described by simple rate theories.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition to the sums-of-exponentials modeling, we also applied a distributed lifetime model based on a quadratic programming algorithm, as discussed previously. 16,46 We have applied both methods of analysis to the full set of data for concentration-dependent fluorescence quenching of 9,10-DCNA by the five cyano anion ILs. The distributed exponential analysis of 9,10-DCNA quenching by C(CN) 3 − in Im 2,1 + / NTf 2 − is given in the Supporting Information.…”
Section: ■ Introductionmentioning
confidence: 99%